Clinical Outlook of Enterococcal Infections and their Antibiogram at a Tertiary Care Facility - Pheba Sholy; Kuruvilla Thomas S (RGUHS Journal of Allied Health Sciences)
Background Enterococci are facultative anaerobic gram-positive cocci occurring in pairs or short chains belonging to the family Enterococcaceae. They are catalase negative and are distributed widely in nature. There are many species of Enterococci that have been identified. The purpose of this study was to determine the frequency of different species of Enterococci from clinical samples with positive culture using conventional methods and to analyze their antibiogram to initiate appropriate therapy.Methods Out of a total 1200 clinical samples processed 59 Enterococcal isolates were obtained from urine pus blood and wound swabs over a period of one year from all the patients admitted to our tertiary care centre. These samples were subjected to culture and sensitivity tests. All the suspected Enterococcal culture isolates were identified by conventional methods and their antibiogram was analyzed.Results The Enterococcal species commonly isolated in our study were E. feacalis and E. feacium. There was a predominance of E. faecalis 33 55.9 over E. faecium 26 44.06 among the 59 Enterococcal infections. E. faecium was found to be multidrug resistant and sensitive only to Vancomycin.Conclusion There was a predominance of E. faecalis over E. faecium among the Enterococcal isolates. The multidrug resistant pattern of E. faecium warrants prompt identification and long term strategies to address the increasing frequency of antibiotic resistance among Enterococcal infections particularly with reference to E. faecium especially when empirical therapy must be initiated.